Reintegration of former child soldiers in northern Uganda: Coming to terms with children's agency and accountability - Akello, Grace; Richters, Annemiek; Reis, Ria (Intervention, 2006)
Reintegration processes of formerly abducted children have yielded limited success in northern Uganda. The article seeks answers to the question why reintegration processes in the area have failed. The approach of one Christian non-governmental organization towards reintegration is compared with the ideas and strategies of formerly abducted child soldiers and people in their communities on how best to deal with their violent past.
Keywords: cen; Child soldiers; Psychotrauma; Reintegration; Uganda; WorldVision